Magnetic Resonance Imaging in degenerative disease of the lumbar spine: Fat Saturation technique and contrast medium - D’Aprile, Paola; Nasuto, Michelangelo; Tarantino, Alfredo; Guglielmi, Giuseppe; Jinkins, J. Randy; Cornacchia, Samantha (Acta Biomedica Atenei Parmensis, 2018)
Purpose: To examine both anterior and posterior elements of the lumbar spine in patients with low back pain using MRI T2-weighted sequences with Fat Saturation (FS) and contrast enhanced T1-weighted sequences with FS. Materials and methods: Two thousand eight hundred and twenty (2820) patients (1628 male, 1192 female, mean age 54) presenting low back pain underwent MRI standard examination (Sagittal T1w TSE and T2w TSE, axial T1 SE) with the addition of sagittal and axial T2w Fat Sat (FS) sequences. Among all the patients, 987 (35%) have been studied adding Contrast Enhanced (CE) T1w FS sequences after administration of contrast medium. Results: Among 987 patients studied with contrast medium, we found: active-inflammatory intervertebral osteochondrosis in 646 (65%) patients; degenerative-inflammatory changes in facet joints (facet joint effusion, synovitis, synovial cysts) in 462 (47%); spondylolysis in 69 (7%); degenerative-inflammatory changes of the flava, interspinous and supraspinous ligaments in 245 (25%); inflammatory changes of posterior perispinal muscles in 84 (8%) patients. Conclusions: In patients with suspected no-disc-related low back pain, the implementation of T2w FS and CE T1w FS sequences to the standard MR protocol could allow a better identification of degenerative-inflammatory changes more likely associated to the pain.